THE INVESTIGATION OF THE EFFECT OF SPORTS ON PERSONALITY - Tazegul, unsal (IJRDO- Journal of Educational Research, 2016)
Purpose of this study is to determine the impact of sport on personality. The sample of the study is made up of 50 university students who do not exercise regularly and participate in the study voluntarily. The students participating in the study are given fitness training 4 days a week for 3 months. To determine the personality of the students participating in the study to assess personality characteristics Adjective Based Personality Test (SDKT) developed by Bacanlı et al (2009) was used. SPSS 20 software package was used to analyze the data obtained. Supplementary statistics and co-sample t-test were used to analyze the data. Following 3 month sports training, a reduction in the trait of neuroticism, and an increase in extraversion, complaisance, and responsibility dimensions have been determined. At the end of the study, it was determined that the sport has a positive influence on the personality. In this study and many other studies carried out before, it has emerged that the sport has an important role in personality development and socializing.